Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s00198-015-3096-z
|View full text |Cite|
|
Sign up to set email alerts
|

Intraoperative detection of viable bone with fluorescence imaging using Visually Enhanced Lesion Scope in patients with bisphosphonate-related osteonecrosis of the jaw: clinical and pathological evaluation

Abstract: The surgical treatments that were exactly performed using MBFT with VELscope® offered successful management of BRONJ. This bone fluorescence helped to define the margins of resection, thus improving surgical therapy for extended osteonecrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
(58 reference statements)
0
7
0
4
Order By: Relevance
“…Tetracycline-fluorescence-guided bone surgery represents a solution for this shortcoming [10,[21][22][23]. The use of tetracycline as a fluorochrome has made it possible, under the appropriate excitation light and filter (VELscope Vx system® fluorescence lamp), to improve the definition of the transition between necrotic (no fluorescence) and non-necrotic (green fluorescence) bone during surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Tetracycline-fluorescence-guided bone surgery represents a solution for this shortcoming [10,[21][22][23]. The use of tetracycline as a fluorochrome has made it possible, under the appropriate excitation light and filter (VELscope Vx system® fluorescence lamp), to improve the definition of the transition between necrotic (no fluorescence) and non-necrotic (green fluorescence) bone during surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Pautke et al (2006) reported periods that range from days to "several weeks", whereas Dahners and Bos (2002) recommend extended periods that range from 3 to 6 months in order to avoid faint labeling. Yoshiga et al (2015b) reported a series in which at least 10 d of tetracycline administration seemed enough so as to differentiate between fluorescent and nonfluorescent areas. In our experience, the most glowing tetracycline uptake was achieved in that case in which the antibiotic had been administered for 4 weeks (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Their full text was assessed for eligibility, and 23 papers that did not conform to the main criteria were excluded. Finally, surgery was performed in the severe MRONJ in a total of 18 papers that were for the literature review [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] ( Figure 1 ). The detailed data of elderly patients (age ≥ 60 years) were found in the 9 papers [ 20 , 21 , 22 , 23 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%